The Role of SME Suppliers in Implementing Sustainability - Meqdadi, Osama; Johnsen, Thomas; Joh, Rhona (Piccola Impresa / Small Business, 2012)
This paper explores sustainability in supply network from a small and medium-sized enterprise (SME) perspective. The paper provides a literature review of sustainability in supply chains and networks and defines related concepts and approaches. Two pilot case studies have been conducted in France exploring how large manufacturing companies engage SME suppliers in sustainability initiatives and the barriers and drivers for SME suppliers in becoming involved in such intitiatives. The results provide tentative support for previous studies that suggest that a mentoring approach rather than a control or monitoring approach is more effective in fully engaging SME suppliers in sustainability initiatives.